Pengaruh Media Sosial Pada Persepsi Publik Terhadap Sistem Peradilan: Analisis Sentimen di Twitter - N. Muhammad, Rivaldhy; Wulandari S, Lestari; Tanggahma, Biloka (LPPM Universitas Ekasakti Padang, 2024)
Social media has become a major platform for the public to express their views on various issues, including the judicial system. This study aims to analyze the influence of social media, particularly Twitter, on public perception of the judicial system in Indonesia. The method used in this research is sentiment analysis applied to thousands of tweets related to judicial issues. Data were collected using data mining techniques and analyzed to identify positive, negative, and neutral sentiments towards the judicial system. The results show that the majority of sentiments expressed by the public on Twitter tend to be negative, reflecting widespread dissatisfaction with the judicial system. Positive sentiments emerged in the context of policy reforms and legal transparency, while negative sentiments were often linked to issues of corruption and injustice. In conclusion, social media, especially Twitter, significantly influences public perception and can serve as an important source for understanding public opinion on the judicial system.